SARS‐CoV‐2 N Protein Induces Acute Kidney Injury via Smad3‐Dependent G1 Cell Cycle Arrest Mechanism. Issue 3 (23rd November 2021) - Wang, Wenbiao; Chen, Junzhe; Hu, Dingwen; Pan, Pan; Liang, Liying; Wu, Wenjing; Tang, Ying; Huang, Xiao R.; Yu, Xueqing; Wu, Jianguo; Lan, Hui Y.
Abstract: COVID‐19 is infected by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and can cause severe multiple organ injury and death. Kidney is one of major target organs of COVID‐19 and acute kidney injury (AKI) is common in critically ill COVID‐19 patients. However, mechanisms through which COVID‐19 causes AKI remain largely unknown and treatment remains unspecific and ineffective. Here, the authors report that normal kidney‐specifically overexpressing SARS‐CoV‐2 N develops AKI, which worsens in mice under ischemic condition. Mechanistically, it is uncovered that SARS‐CoV‐2 N‐induced AKI is Smad3‐dependent as SARS‐CoV‐2 N protein can interact with Smad3 and enhance TGF‐ β /Smad3 signaling to cause tubular epithelial cell death and AKI via the G1 cell cycle arrest mechanism. This is further confirmed in Smad3 knockout mice and cells in which deletion of Smad3 protects against SARS‐CoV‐2 N protein‐induced cell death and AKI in vivo and in vitro. Most significantly, it is also found that targeting Smad3 with a Smad3 pharmacological inhibitor is able to inhibit SARS‐CoV‐2 N‐induced AKI. In conclusion, the authors identify that SARS‐CoV‐2 N protein is a key mediator for AKI and induces AKI via the Smad3‐dependent G1 cell cycle arrest mechanism. Targeting Smad3 may represent as a novel therapy for COVID‐19‐asscoaited AKI. Abstract : In this article, the authors discover that severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) N protein can bind and activate Smad3 to induce kidney cell death and cause acute kidney injury (AKI) via p21‐dependent G1 cell cycle arrest mechanism. Targeting Smad3 with a pharmacological inhibitor SIS3 can inhibit SARS‐CoV‐2 N‐induced AKI.